2022
DOI: 10.1039/d1gc03901f
|View full text |Cite
|
Sign up to set email alerts
|

Chemically recyclable polymer materials: polymerization and depolymerization cycles

Abstract: Design and synthesis of chemically recyclable polymers, which can be reutilized as their starting monomers or new value-added chemicals, have provided a practical approach to address the end-of-use problem of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
96
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 239 publications
(239 reference statements)
1
96
0
4
Order By: Relevance
“…Our research group is committed to finding out versatile depolymerization catalysts to achieve the degradation of various polymer materials. In our previous studies, we found that zinc bis­[bis­(trimethylsilyl)­amide] [Zn­(HMDS) 2 ], as a multifunctional transesterification catalyst, can promote the chemical recycling of PLA and PCL to value-added chemicals. Based on that, in this work we further broaden the application fields for the selective catalysis depolymerization of plastic materials, including PLA, BPA-PC, PBS, PBAT, PCL, and PET. The degradation processes and influencing factors of a single polyester and polycarbonate plastics were explored first.…”
Section: Introductionmentioning
confidence: 93%
“…Our research group is committed to finding out versatile depolymerization catalysts to achieve the degradation of various polymer materials. In our previous studies, we found that zinc bis­[bis­(trimethylsilyl)­amide] [Zn­(HMDS) 2 ], as a multifunctional transesterification catalyst, can promote the chemical recycling of PLA and PCL to value-added chemicals. Based on that, in this work we further broaden the application fields for the selective catalysis depolymerization of plastic materials, including PLA, BPA-PC, PBS, PBAT, PCL, and PET. The degradation processes and influencing factors of a single polyester and polycarbonate plastics were explored first.…”
Section: Introductionmentioning
confidence: 93%
“…The problem of plastic waste is so vital that their weight in the ocean will be as much as fish by 2050 if no solutions are found for their recycling or biodegradability. 269 Although the plastic materials are under pressure to be redesigned to meet recyclability criteria, there are some challenges in polyolefin recycling, such as the product low value and the lack of secondary markets, problems in sorting the mixed waste, and the thermodynamically unfavorable C−C bond dissociation. 270,271 Generally, polyolefin recycling technologies are classified as primary or re-extrusion, secondary or mechanical, tertiary or chemical, and quaternary or energy recovery.…”
Section: Recyclabilitymentioning
confidence: 99%
“…However, the massive production of plastic wastes has caused severe crises, polluting the environment and threatening the global climate goals. , To address these issues, increasingly more attention has been paid to the sustainability of plastics. Chemically recyclable polymers represent an effective solution to solve the end-of-use problem of plastics, which could be transformed into their starting monomers or new value-added chemicals. While referring to this subject, in addition to developing new plastics, recycling of plastic materials currently widely used, such as poly­(bisphenol A carbonate) (BPA-PC), should urgently be taken into account.…”
Section: Introductionmentioning
confidence: 99%